Synthesis of functional nonwoven fabric using radiation grafting for the selective adsorption of Au(Ⅲ) in an acidic solution - FENG Xinxin; MAO Xuanzhi; ZHANG Mingxing; HU Lijun; HAN Hongwei; XING Zhe; LI Rong; WU Guozhong (Fushe yanjiu yu fushe gongyi xuebao, 2023)
Herein, a bifunctional nonwoven fabric sorbent containing thioamide and carboxyl groups was synthesized via radiation grafting of acrylonitrile and acrylic acid, followed by modification with sodium sulfide, to selectively recover Au(Ⅲ) from the acidic solution. A polyethylene/polypropylene skin-core-structured nonwoven fabric was used as the substrate. The structure and properties of the sorbent were characterized using infrared spectroscopy, thermogravimetric analysis, scanning electron microscopy, energy dispersive spectroscopy, contact angle measurements, X-ray photoelectron spectroscopy, and X-ray diffraction. The adsorption performance of the sorbent was determined through batch adsorption tests. The results indicated that the sorbent exhibited excellent Au‍(Ⅲ) adsorption capacity over a wide pH range (2-7) and demonstrated good selectivity for Au(Ⅲ) in the presence of coexisting metal ions, with selectivity coefficients ranging from 55.00 to 2 429.17 and a gold recovery ratio of 98.5%. The adsorption followed the pseudo-second-order kinetic and Langmuir isotherm models, with an Au(Ⅲ) saturation adsorption capacity of 133.91 mg/g. Au(Ⅲ) could be reduced to crystalline Au(0) during the adsorption process. Moreover, the modified nonwoven fabric could be effectively removed via simple high-temperature treatment, facilitating Au recovery.